Voltaire and the century of light - Aldridge, Alfred Owen, 1915-2005 (Princeton legacy library., 1975)
Taking an approach different from (hat of earlier biographers, A. Owen Aldridge examines Voltaire's literary and intellectual career chronologically, using the methods both of comparative literature and of the history of ideas. The resulting biography portrays a fascinating personality as well as a great writer and thinker. Voltaire is revealed not only through his correspondence, here extensively "ed, but through the statements others made about him in anecdotes, memoirs, and other contemporary documents. New information is introduced regarding Voltaire's sojourn in England, his later relations with English men of letters, his domestic turmoils at the court of Frederick the Great, and his contact with French contemporaries such as Montesquieu and Diderot. For the first time in any biography, attention is given to Voltaire's extensive knowledge of Spanish literature and its influence on his own work, particularly Candide. Voltaire is portrayed as a conscious participant in the Enlightenment. In his early years he was interested primarily in aesthetics and abstract philosophy; later, he passionately dedicated himself to humanitarian causes with ideological implications. Professor Aldridge brings forward evidence pointing to the contrast between these two periods in Voltaire's life. Originally published in 1975. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905